RUANG LINGKUP MANAJEMEN STRATEGIK - Andi Nur Asnani Nasmin; Andi Nirmayanthi, St. Syamsudduha, Mardhiah Hasan; Mujahidah (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Strategic management is a crucial process in organizational management aimed at achieving its long-term goals. The scope of strategic management will be elaborated with a focus on the key elements involved. Firstly, the analysis of the external and internal environment forms the basis for understanding the context in which the organization operates, as well as identifying opportunities and challenges. Secondly, setting vision, mission, and core strategies provides clear direction and goals for the organization. Thirdly, operational planning details the concrete steps to implement the established strategies, including resource allocation and performance measurement. Lastly, the involvement of top management is essential in leading, motivating, and ensuring alignment between organizational strategies and long-term goals. By understanding and implementing this scope of strategic management, organizations can achieve a competitive advantage and reach their long-term objectives amidst dynamic changes in the business environment.